Alzheimer's disease in the human eye. Clinical tests that identify ocular and visual information processing deficit as biomarkers. Issue 2 (9th September 2013) - Chang, Lily Y.L.; Lowe, Jennifer; Ardiles, Alvaro; Lim, Julie; Grey, Angus C.; Robertson, Ken; Danesh‐Meyer, Helen; Palacios, Adrian G.; Acosta, Monica L.
Abstract: Alzheimer's disease (AD) is the most common form of dementia with progressive deterioration of memory and cognition. Complaints related to vision are common among AD patients. Several changes in the retina, lens, and in the vasculature have been noted in the AD eye that may be the cause of visual symptoms experienced by the AD patient. Anatomical changes have been detected within the eye before signs of cognitive impairment and memory loss are apparent. Unlike the brain, the eye is a unique organ that can be visualized noninvasively at the cellular level because of its transparent nature, which allows for inexpensive testing of biomarkers in a clinical setting. In this review, we have searched for candidate biomarkers that could enable diagnosis of AD, covering ocular neurodegeneration associated with functional tests. We explore the evidence that suggests that inexpensive, noninvasive clinical tests could be used to detect AD ocular biomarkers.